BILATERAL SIMULTANEOUS CENTRAL RETINAL VEIN OCCLUSION IN A PATIENT WITH SYSTEMIC HYPERTENSION - Basim Mubarik; Aamir Ali Choudhry (Journal of University Medical & Dental College)
ABSTRACT The central retinal vein occlusion is caused by age related changes in the retinal vessels. Bilateral central retinal vein occlusion is a relatively rare event. Only less than 10% cases are bilateral. While simultaneous bilateral central retinal vein occlusion is very rare. We are presenting a case report regarding a middle aged hypertensive patient who presented with bilateral central retinal vein occlusion in the Department of Ophthalmology, Madina Teaching Hospital, Faisalabad. A 55 years old middle aged female presented with bilateral sudden blurring of vision with finger counting vision in both eyes. After detailed clinical work up a diagnosis of bilateral central retinal vein occlusion secondary to systemic hypertension was made. Her hypertension was controlled with the help of internist and constant follow up was advised.